HHhH - Camacho Arango, Carlos (Revista de Historia Iberoamericana, 2013)
<ul id="informacion" style="margin: 0px; padding: 0px; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-stretch: inherit; font-size: 12px; line-height: inherit; font-family: Arial, Helvetica, sans-serif; vertical-align: baseline; list-style: none;"> Es reseña de: <p class="titulo" style="margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: 13px; line-height: inherit; font-family: inherit; vertical-align: baseline;"><span class="titulo" style="margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: bold; font-stretch: inherit; font-size: inherit; line-height: inherit; font-family: inherit; vertical-align: baseline;"><a style="margin: 0px; padding: 0px; border: 0px; font: inherit; vertical-align: baseline; text-decoration-line: none; color: #990000; outline: none 0px; cursor: pointer;" href="https://dialnet.unirioja.es/servlet/libro?codigo=845442">HHhH <a style="margin: 0px; padding: 0px; border: 0px; font: inherit; vertical-align: baseline; text-decoration-line: none; color: #990000; outline: none 0px; cursor: pointer;" href="https://dialnet.unirioja.es/servlet/autor?codigo=3003904">Laurent Binet, <a style="margin: 0px; padding: 0px; border: 0px; font: inherit; vertical-align: baseline; text-decoration-line: none; color: #990000; outline: none 0px; cursor: pointer;" href="https://dialnet.unirioja.es/servlet/autor?codigo=5461707">Adolfo García Ortega Seix Barral, 2011. <acronym style="margin: 0px; padding: 0px; border: 0px; font: inherit; vertical-align: baseline; cursor: help;" title="International Standard Book Number" xml:lang="en">ISBN</acronym> 978-84-322-0932-1